1998
DOI: 10.1007/s003830050399
|View full text |Cite
|
Sign up to set email alerts
|

Retinol status of newborn infants with congenital diaphragmatic hernia

Abstract: The etiology of congenital diaphragmatic hernia (CDH) is not yet known. Studies in the literature from 1941 have reported that nutritional deficiency of vitamin A during pregnancy could lead to CDH, associated or not with other malformations in young rats. More recently, possible correlations between expression patterns of cellular retinoid-binding protein and retinoic-acid receptors and morphologic effects of vitamin A deficiency have been suggested. The purpose of this study was to verify in human newborns t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 9 publications
3
93
1
Order By: Relevance
“…Although the mechanism by which nitrofen induces the diaphragmatic defect and lung hypoplasia is not fully understood, recent evidences suggest the involvement of abnormalities linked with the retinoid signaling pathway in this model and also in human CDH etiology (42)(43)(44)(45). Indeed, one clinical study demonstrated the presence of decreased levels of retinol and retinol-binding protein in human CDH, suggesting a possible deterioration of retinol transport across the placenta (46). Regarding the nitrofen-induced CDH model, it was already demonstrated that nitrofen inhibits retinal dehydrogenase 2 (RALDH2), a key enzyme responsible for the conversion of retinal to retinoic acid (47).…”
Section: Discussionmentioning
confidence: 90%
“…Although the mechanism by which nitrofen induces the diaphragmatic defect and lung hypoplasia is not fully understood, recent evidences suggest the involvement of abnormalities linked with the retinoid signaling pathway in this model and also in human CDH etiology (42)(43)(44)(45). Indeed, one clinical study demonstrated the presence of decreased levels of retinol and retinol-binding protein in human CDH, suggesting a possible deterioration of retinol transport across the placenta (46). Regarding the nitrofen-induced CDH model, it was already demonstrated that nitrofen inhibits retinal dehydrogenase 2 (RALDH2), a key enzyme responsible for the conversion of retinal to retinoic acid (47).…”
Section: Discussionmentioning
confidence: 90%
“…9,10 In 1994, Mendelsohn and colleagues 11 published data showing that in a subset of double-retinoic acid receptor subtype knockouts, fetuses had diaphragmatic hernias. Major and colleagues 12 provided preliminary evidence supporting a role of vitamin A as a factor in human CDH. In a small study of human mothers and infants born with or without CDH, it was reported that the retinol levels in the maternal and infant plasma were abnormal when CDH was present.…”
Section: 2mentioning
confidence: 98%
“…Newborns with CDH show reduced concentrations of retinol and retinol binding protein (RBP) in cord blood compared with healthy newborns (Major et al, 1998;Beurskens et al, 2010). However, the retinol and RBP concentrations at birth seem not to be deranged in the mothers of these children (Major et al, 1998;Yang et al, 2008;Beurskens et al, 2010).…”
Section: Introductionmentioning
confidence: 99%